Effects of Combined Surfaces vs. Single-Surface Plyometric Training on Soccer Players' Physical Fitness. Issue 9 (September 2020) - Ramirez-Campillo, Rodrigo; Álvarez, Cristian; García-Pinillos, Felipe; García-Ramos, Amador; Loturco, Irineu; Chaabene, Helmi; Granacher, Urs
Abstract : Abstract: Ramirez-Campillo, R, Álvarez, C, García-Pinillos, F, García-Ramos, A, Loturco, I, Chaabene, H, and Granacher, U. Effects of combined surfaces vs. single-surface plyometric training on soccer players' physical fitness. J Strength Cond Res 34(9): 2644–2653, 2020—The aim of this study was to compare the effects of a 8-week plyometric jump training (PJT) performed on different surfaces (grass, land-dirt, sand, wood, gym mat, and tartan-track) vs. a single-surface PJT (grass) on components of physical fitness (muscle power, speed, and change-of-direction speed [CODS] tasks) and sport-specific performance (i.e., maximal kicking velocity [MKV]) in male soccer players aged 11–14 years. Athletes were randomly assigned to a combined surfaces PJT (PJTc, n = 8), a single-surface PJT (PJTs, n = 8), or an active control (CON, n = 7). Although the PJT group trained on grass, the PJTc trained on 6 different surfaces and equally distributed the total jump volume according to the surface. Pre-post tests were conducted on grass. Significant main effects of time were observed for the countermovement jump, the standing-long-jump, the 20-cm drop jump, 30-m sprint time, CODS, and MKV (all p < 0.001; d = 0.53–0.87). Group × time interactions were identified for all jump tests, MKV, 30-m sprint time, and CODS (all p < 0.001; d = 0.58–0.71) in favor of PJTc. No significant pre-post changes were observed in the CON (all p > 0.05; d = 0.07–0.1). In conclusion, PJT is effective in improving physical fitness in young soccer players when conducted in combination with regular soccer training. Although general fitness testing and PJTs were performed on grass, larger physical fitness improvements were found after PJTc. Thus, PJTc is recommended, as it provides a better overload stimulus compared with more conventional training overload (e.g., increase in training volume or intensity). Future studies still have to address the underlying physiological adaptations after PJTc.